Cognition and Understanding of Neuropathy of Inpatients Admitted to a Specialized Tertiary Diabetic Foot Unit With Diabetes-Related Foot Ulcers. (September 2019) - Corbett, Claire; Jolley, Jane; Barson, Elizabeth; Wraight, Paul; Perrin, Byron; Fisher, Caroline
This study investigated cognitive functioning and understanding of peripheral neuropathy in a cohort of individuals with diabetes-related foot ulcers requiring hospitalization. The aim was to examine the association between cognition, understanding of peripheral neuropathy, and diabetic health variables. Thirty inpatients referred to the Diabetic Foot Unit Clinical Psychology service, at the Royal Melbourne hospital, were assessed using the Montreal Cognitive Assessment (MoCA) and the Patient Interpretation of Neuropathy (PIN) questionnaire. Relevant demographic and medical information was collected. In this predominantly middle-aged, male cohort, the average MoCA score (22.37, SD = 3.65) fell below the general population age-matched mean, and a quarter of the MoCA patient scores were consistent with those seen in early dementia samples (<20). There appeared to be several misperceptions regarding peripheral neuropathy, less accurate attributions of blame to self or practitioners, and more accurate attributions of control of ulcer management to practitioners. Correlation analysis indicated that individuals with stronger MoCA scores tended to provide more accurate answers on the Acute Foot Ulcer Onset PIN scale. Individuals with diabetes-related foot ulcers requiring hospitalization demonstrate reduced cognitive functioning and this may affect their understanding of peripheral neuropathy, particularly information regarding foot ulcer onset. Routine screening of cognitive functioning in this cohort may be useful so that health education and care management can be adjusted according to individual patients' cognitive capabilities.